KETIDAKMAMPUAN MEMBAYAR UTANG DALAM PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG OLEH MANTAN PILOT LION AIR - Luthfatun Mawwaddah (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2020)
AbstractAn alternative that can be taken to overcome the problem of fulfilling debt payment obligations is to postpone the Obligation of Debt Payment Obligations (PKPU), such as the submission of PKPU done by former Lion Air pilots with Case Number 196 / Pdt.Sus-PKPU / 2019 / PN Niaga Jkt.Pst which won the suit of former Lion Air pilot. However, the results of the decision were not carried out by Lion Air. his writing aims to find out the meaning of the condition of